1990
DOI: 10.1111/j.1365-2125.1990.tb03808.x
|View full text |Cite
|
Sign up to set email alerts
|

D‐penicillamine and D‐penicillamine‐protein disulphide in plasma and synovial fluid of patients with rheumatoid arthritis.

Abstract: 1 The plasma pharmacokinetics of D-penicillamine (D-pen) and D-penicillamine-albumin disulphide (D-pen-alb) were examined over a dosage interval in six patients with rheumatoid arthritis. In two of these, 24 h synovial fluid profiles of D-pen and D-pen-alb were also obtained. 2 D-pen was undetectable in plasma at the beginning of the study. The peak concentration (5.4 ± 1.2 FM) occurred at between 45 min and 2 h and the mean elimination half-life was 0.6 h. D-pen-alb, however, was present at a mean plasma con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 19 publications
(23 reference statements)
1
13
0
Order By: Relevance
“…403 Peak concentrations of the albumin conjugate were also variable after single doses, and exceeded peak penicillamine concentrations in samples collected more than 3 hours postdose (Joyce et al 1991). Mean steady-state concentrations (± SEM) of penicillamine have been reported to be 5.4 ± 1.2 Jlmol/L, and the concentration of the albumin conjugate was about 5 times as high (Joyce & Day 1990). These variable concentrations of reduced penicillamine, and the albumin conjugate reservoir, may contribute to the variable clinical response noted with this drug.…”
Section: Variability In Responsementioning
confidence: 91%
See 2 more Smart Citations
“…403 Peak concentrations of the albumin conjugate were also variable after single doses, and exceeded peak penicillamine concentrations in samples collected more than 3 hours postdose (Joyce et al 1991). Mean steady-state concentrations (± SEM) of penicillamine have been reported to be 5.4 ± 1.2 Jlmol/L, and the concentration of the albumin conjugate was about 5 times as high (Joyce & Day 1990). These variable concentrations of reduced penicillamine, and the albumin conjugate reservoir, may contribute to the variable clinical response noted with this drug.…”
Section: Variability In Responsementioning
confidence: 91%
“…The half-life of the disu1phide conjugate with albumin was reported to be approximately 36 hours (Joyce & Day 1990;Joyce et al 1991), compared with a half-life reported for penicillamine itself of 0.6 to 3 hours (Bergstrom et al 1981;Brooks et al 1984;Joyce & Day 1990;Osman et al 1983).…”
Section: Eliminationmentioning
confidence: 93%
See 1 more Smart Citation
“…For example, N-acetyl-L-cysteine (and L-cysteine) binds to albumin in plasma; the interaction can be quantitated by a high-performance liquid chromatographic (HPLC) method using hexaiodoplatinate. 36) Furthermore, D-penicillamine, 32,37) captopril, 32,33) meso-2,3-dimercaptosuccinate, 38) and SA3786 (a bucillamine derivative) 39) bind to albumin in the serum of patients receiving these drugs. Interestingly, the reactivity in patient sera is much higher than that found in albumin solutions 33) and in sera of healthy volunteers.…”
Section: Ligand Bindingmentioning
confidence: 99%
“…Low molecular weight disulfides are the major products of D-PA metabolism in humans. 9 The oxidation of D-PA in vivo may also important in the mode of action of the drug through simultaneous reduction of the ROS and reactive nitrogen species (RNS). Consequently, D-PA fulfils the criteria of a hybrid drug in the neonatal period by its ability to modulate both oxidative stress and NO pathway, and can be a neuroprotective agent in the pathophysiology of neurologic dysfunction (Figure 1).…”
Section: Introductionmentioning
confidence: 99%